Prospect of Dairy Cattle Development Outside Java Island to Support Milk Self Sufficiency in Indonesia - Matondang, Rasali Hakim; Talib, Chalid; Herawati, Tati (Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
Dairy cattle in Indonesia have known as Holstein Friesian (FH) cows with the highest milk production in the world. The cow have a good adaptability to subtropical to tropical climate, and from highlands to lowlands. The FH cows grow quite well in areas with an altitude of more than 700 m above sea level as well as in lowland areas with a range of 0 â 300 m above sea level such as in Pasuruan (East Java), Sumedang (West Java), and Kampar (Riau). FH cows produce milk in a range between 3000 â 4000 liters per lactation or an average of 10.7 liter/head/day. Indonesia has a good prospect to develop dairy industry due to a potential of population that nearly to 240 million people. Milk consumption tends to increase along with growth on economic and income per capita of Indonesia people. Domestic milk production has only reached 30% of national demand. Up to the moment, production center of dairy population has concentrated in Java (99%), even though it has limitation on land availability and feed sources. Therefore, the development of dairy industry outside of Java need to be supported as the strengths to do are available such as a market potential for fresh milk, adaptability of climate and local feed resources. The central and provincial government have to accelerate the roles on facilitation and regulation including easily access to financial sources to get liability of commercial credit for farming business. Key words: Dairy cow, outside java, milk self-sufficiency